Clinical Outcome of Cytomegalovirus Infection on Low Birth Weight Infants - Usman, Ali; Sukadi, Abdurachman; Mose, Johannes C (Fakultas Kedokteran Universitas Islam Bandung, 2014)
Abstract Cytomegalovirus (CMV) is a DNA virus and a marker of the herpes virus groups. This virus was found only in human and the infection occurs for a long time. The transmission of CMV infection to fetus/neonates is via congenital infections or perinatal infections. Clinical manifestation of symptomatic CMV infection of the fetus has two presentations, early and second early manifestations. Diagnosis of neonatal CMV infection may be done by serologic test based on detection of IgM of CMV infection. The objective of this study is to asses clinical outcome of CMV infection of low birth weight infants delivery with long term sequelae. An observational study was conducted since March 2010 until December 2011 in Advent and Hermina Pasteur Hospital, all subjects were low birth weight infants (LBWI). The inclusion criterias are all LBWI who were delivered in those hospital or were a referred neonates. The exclusion criterias are major congenital defect, which is not related to congenital CMV infection and neonatesâ death before one week of life. Every neonate was examine both their physical and peripher blood count, glucose, Ca.Â Liver function test done for neonates with acute hepatitis and titre IgG and IgM CMV serial, head ultrasound serial and head CT scan/MRI used for babies with intracranial bleeding and hydrocephaly. Â During the period of this study there were 50 cases of LBWI, consisted of 41 preterm babies, and 30 small for gestational age babies. Clinical manifestation of acute hepatitis were found in 20% subjects, all of them with the Â elevation of liver function test. Microcephaly which occured in the first untill three weeks of life were 8%. Ventricular dilatation were 10% in the first week of life and increased up to 48% after three weeks. Cases with intracranial haemorrhage were found in 6% and 10% with cerebral calcification on head while sensorineural hearing loss were 8%. All of LBWI have 100% serorespon immune IgG. IgM CMV reactive only in 12% cases but after 3 weeks increased up to 32%. During neonatal up to infancy period, the prevalence of CMV infection in Bandung is high (12+32%:44%) with long term sequelae which are serious and can be fatal. It is urgent and important to give information about this disease to new couples, every mother and healthcare providers in fetomaternal fields to preventÂ CMV infection. Â Key words CMV infection, long term sequelae, outcomeÂ Abstract Cytomegalovirus (CMV) adalah virus DNA dan termasuk dalam kelompok virus herpes. Virus ini hanya menyerang manusia dan infeksinya berlangsung lama. Penularan CMV pada janin/neonatus dapat melalui infeksi kongenital atau infeksi perinatal. Manifestasi Infeksi CMV pada janin terdiri dari dua bentuk yaitu manifestasi awal dan lanjut. Diagnosis infeksi CMV neonatal ditegakkan dengan tes serologis berdasarkan deteksi IgM CMV. Tujuan penelitian ini adalah menilai keluaran klinis infeksi CMV pada bayi berat lahir rendah dengan gejala sisa. Penelitian observasional telah dilakukan sejak Maret 2010 sampai dengan Desember 2011 di RS Advent dan RS Hermina Pasteur pada semua bayi berat lahir rendah (BBLR). Kriteria inklusi adalah semua BBLR yang lahir di kedua RS maupun merupakan pasien rujukan. Kriteria eksklusi adalah adanya kelainan kongenital mayor yang tidak berhubungan dengan infeksi CMV kongenital dan bayi yang meninggal dalam minggu pertama. Setiap bayi dilakukan pemeriksaan fisik dan laboratorium (hitung darah tepi, kadar glukosa dan kalsium), tes fungsi hati dilakukan pada bayi yang menderita hepatitis akut, pemeriksaan kadar IgG dan IgM CMV serial, USG kepala dan CT scan/MRI kepala pada kasus hidrocefalus dan perdarahan intrakranial. Selama penelitian terdapat 50 kasus BBLR yang terdiri dari 41 bayi prematur, 30 bayi kecil masa kehamilan. Hepatitis akut ditemukan sebanyak 20% yang semuanya disertai peningkatan tes fungsi hati. Mikrosefali yang terjadi sampai usia 3 minggu sebanyak 8%. Dilatasi ventrikular lateralis sebesar 10% pada minggu pertama dan meningkat sebanyak 48% setelah 3 minggu. Perdarahan intrakranial sebanyak 6% dan kalsifikasi serebral 10%. Gangguan pendengaran sebanyak 8%. IgG (+) pada semua BBLR (100%). IgM CMV reaktif hanya 12% tetapi meningkat sebesar 32% setelah usia 3 minggu. Simpulan penelitian ini adalah prevalensi infeksi CMV di Bandung cukup tinggi (12+32%:44%) dengan gejala sisa neurologis yang berat dan fatal selama 6 bulan postnatal, sehingga perlu diberikan informasi mengenai penyakit ini kepada pasangan baru, setiap ibu dan petugas kesehatan di bidang fetomaternal untuk mencegah infeksi ini. Kata kunci: Gejala sisa jangka panjang, Infeksi CMV, keluaranÂ